2018
DOI: 10.26480/aim.01.2018.01.03
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Intrinsic Motivation Between Transformational Leadership And Creativity

Abstract: The current article is a literature review on the mediating role of intrinsic motivation between transformational leadership and creativity. However, past studies conducted on the role of intrinsic motivation as a mediator between transformational leaders and creativity has produced mixed results. Moreover, the lack and significance of creativity in education have been highlighted.Conclusion and future research are written at the end.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The more comfortable the athlete with their coach, the higher the athlete's satisfaction with their performance in the sport. Leadership is widely studied in the management of work organizations such as leadership on employee ethics [7], leadership and creativity [8,9], and servant leadership with organizational goals [10,11] [15], coach leadership and leadership behaviors [16] as well as leadership and internal motivation of athletes [17]. One of the studies that focused on transformational leadership and athlete satisfaction was adopt from [18] who found that there was a positive relationship between the two variables.…”
Section: Introductionmentioning
confidence: 99%
“…The more comfortable the athlete with their coach, the higher the athlete's satisfaction with their performance in the sport. Leadership is widely studied in the management of work organizations such as leadership on employee ethics [7], leadership and creativity [8,9], and servant leadership with organizational goals [10,11] [15], coach leadership and leadership behaviors [16] as well as leadership and internal motivation of athletes [17]. One of the studies that focused on transformational leadership and athlete satisfaction was adopt from [18] who found that there was a positive relationship between the two variables.…”
Section: Introductionmentioning
confidence: 99%